Effect of laser speed on neck formation in SS316L powder joining for LPBF - Mohd Rhafiq, Mazlan; Nashrah Hani, Jamadon; Mohd Azlan, Aripin; Abu Bakar, Sulong; Aiman, Mohd Halil; M., Ishak; Shamini, Janasekaran (Elsevier, 2024)
The objective of this study is to comprehend how changes in laser speed affect the behaviour and features of neck formation in SS316L during powder bed fusion. This study examines the impact of various laser speeds on the neck formation in the commonly used SS316L. Uniweld Laser 3000 was used for laser joining. A constant laser power of 15 W and laser scan speed of 25–150 mm/s were implemented, and powder joining within a single track was observed. Results show that neck size decreases with increasing laser scanning speed and no particle joining occurs at 150 mm/s scan speed, as it is considered too fast for sufficient heat absorption and melting. As laser speed decreases to 125 mm/s, neck starts to form because the particles absorb more heat, which facilitates melting and bonding. Surface diffusion occurs early at this stage because it requires only a small amount of energy to break atomic bonds on the surfaces of particles compared to those in the internal part. This process involves atoms moving along the surfaces of the particles, facilitating the initial stages of sintering by reducing surface energy and causing neck formation between particles. At 125 mm/s, the particle shape remains spherical, and the average neck size is 49 μm. At 100 μm, the powder average neck size is 62 μm. Moreover, the powder completely merges at 50 mm/s and 25 mm/s. The neck formed between particles considerably improves the product's mechanical strength by strengthening bonds between particles. Material density increases with neck quality, and stable neck growth can reduce the porosity of the final parts. Ensuring thermal stability in the laser powder bed fusion allows consistent heat to particles, ensuring even temperature in materials and ultimately facilitating stable neck growth. Thermal stability enables atoms in particles to migrate efficiently and prevents defects, such as bubbling, which increases porosity in printed parts. Therefore, a slow scanning speed allows particles to absorb more heat for melting, increasing the neck size of particles. This knowledge is useful for optimizing laser processing parameters in various industrial applications.